Semitic Poetic Techniques in the Magnificat: Luke 1:46-47, 55 - Mendez, Hugo (Journal of Biblical literature, 2016)
Two peculiar alternations of grammatical form appear in the Magnificat: a tense shift in verses 46b-47 and an alternation of object constructions in verse 55. Though most studies treat these phenomena as outlying examples of Greek usage, a better explanation is found in the marked language character of the canticle itself. A previous study by Randall Buth (1984) has argued that the tense shift in verses 46b-47 reflects a common Semitic poetic device. I defend that analysis and extend it to verse 55, identifying the preposition/case shift there as a second stylistic grammatical alternation in the canticle, specifically: an instance of reversed ballast prepositions. The presence of these devices in the Magnificat demonstrates that its poet possessed an interior grasp of the conventions of Semitic poetry and could execute a hymn in that tradition with skill. Furthermore, with the goal of supplementing inventories of the Magnificat's poetic features, I undertake a literary and linguistic analysis of both devices, giving particular attention to the negotiation of likeness and unlikeness in parallelisms, ambiguity as a vehicle of poetic expression, and the impact of these devices in a Greek presentation.